Bond Wire Damage Detection Method on Discrete MOSFETs Based on Two-Port Network Measurement - Minghui Yun; Miao Cai; Daoguo Yang; Yiren Yang; Jing Xiao; Guoqi Zhang (Micromachines, 2022)
Bond wire damage is one of the most common failure modes of metal-oxide semiconductor field-effect transistor (MOSFET) power devices in wire-welded packaging. This paper proposes a novel bond wire damage detection approach based on two-port network measurement by identifying the MOSFET source parasitic inductance (LS). Numerical calculation shows that the number of bond wire liftoffs will change the LS, which can be used as an effective bond wire damage precursor. Considering a power MOSFET as a two-port network, LS is accurately extracted from frequency domain impedance (Z−parameter) using a vector network analyzer under zero biasing conditions. Bond wire cutoff experiments are employed to validate the proposed approach for bond wire damage detection. The result shows that LS increases with the rising severity of bond wire faults, and even the slight fault shows a high sensitivity, which can be effectively used to quantify the number of bond wire liftoffs of discrete MOSFETs. Meanwhile, the source parasitic resistance (RS) extracted from the proposed two-port network measurement can be used for the bond wire damage detection of high switching frequency silicon carbide MOSFETs. This approach offers an effective quality screening technology for discrete MOSFETs without power on treatment.